Study on Properties of Cold-Sprayed Al-Zn Coating on S135 Drill Pipe Steel - Dongli Lv; Tao Zhang; Feiyang Gong (Advances in Materials Science and Engineering)
With the gradual depletion of shallow resources, the petroleum industry is developing toward ultradeep wells and high-speed drillings, and the problems of corrosion and erosion failure of drill pipe materials are becoming more and more serious. On the basis of not destroying the excellent mechanical properties of S135 drill pipe steel, three kinds of coatings, 20% Al-80% Zn, 30% Al-70% Zn, and 40% Al-60% Zn, are cold sprayed on S135 steel. The morphology of the coating is observed, and the bonding strength, porosity, hardness, and corrosion resistance of the coating are tested. Results show that the bonding mechanism between the powder particles and the substrate of the three coatings is mainly mechanical occlusion. From the substrate to the coating surface, the hardness value decreases gradually. With the increase of Al powder content, coating bonding strength increases, coating becomes more compact, and porosity decreases. Corrosion test results show that three coatings can protect the substrate. The density of corrosion products on the coating surface increased with the increase of the Al content. Corrosion potential of the three coatings is lower than that of the substrate, and the corrosion rate of the three coatings is lower than that of the substrate.